Evaluasi Program Desa Tangguh Bencana dalam Perspektif Flood Risk Management - Oscar Radyan Danar; Tommy Anggriawan; Dellarizki Prameisa (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
Pacitan district is one of the five districts included in the highest disaster risk region in East Java. One of the area with a big threat of destructive flood disaster is Sirnoboyo Village, which is located between Grindulu and Jelok River. An attempt to improve community preparedness in the midst of flood hazard are carried out through Village Disaster Resilience Program. Village disaster resilience program is a form of flood risk management (FRM) as a community-based disaster risk reduction by building up self-sufficiency and adaptation. FRM is a theoritical analytic-based that is used in conjuction with Context, Input, Process, and Product (CIPP) evaluation model. The qualitative-descriptive approach was chosen to describe chronologically the evaluation of village disaster resilience program, which encounters several obstacles such as lack of active community and youth participation and under-capacity of the volunteer team. This study offers a reconstruction of village disaster resilience program execution in accordance with the FRM framework to effectively maximize community readyness over the threat of flood hazard that stakeout throughout a year.